2013
DOI: 10.1111/jpi.12090
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and the theories of aging: a critical appraisal of melatonin's role in antiaging mechanisms

Abstract: The classic theories of aging such as the free radical theory, including its mitochondria-related versions, have largely focused on a few specific processes of senescence. Meanwhile, numerous interconnections have become apparent between age-dependent changes previously thought to proceed more or less independently. Increased damage by free radicals is not only linked to impairments of mitochondrial function, but also to inflammaging as it occurs during immune remodeling and by release of proinflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
253
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(271 citation statements)
references
References 446 publications
7
253
0
5
Order By: Relevance
“…Disruption of the circadian rhythms has been linked to metabolic disorders such as type 2 diabetes (reviewed by [38]). Furthermore, melatonin has been shown to be an immune stimulator (reviewed by [39]) and seems to be directly involved in the modulation of insulin secretion. However the effect of melatonin on insulin secretion is debatable, as melatonin has been shown to inhibit insulin secretion in vivo and in vitro in rodent models, whereas in one study it enhanced insulin secretion in human islets [40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of the circadian rhythms has been linked to metabolic disorders such as type 2 diabetes (reviewed by [38]). Furthermore, melatonin has been shown to be an immune stimulator (reviewed by [39]) and seems to be directly involved in the modulation of insulin secretion. However the effect of melatonin on insulin secretion is debatable, as melatonin has been shown to inhibit insulin secretion in vivo and in vitro in rodent models, whereas in one study it enhanced insulin secretion in human islets [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the observed age-related reduction in endogenous melatonin levels. Reduced melatonin levels have been linked to immunosenescence, a process that is thought to contribute to autoimmune diseases in elderly people (reviewed by [39]). …”
Section: Discussionmentioning
confidence: 99%
“…14,31 Melatonin, the main secretory product of the pineal gland, can easily cross the blood-brain barrier and has plentiful neuroprotective properties such as regulating circadian rhythms and providing anti-inflammatory and neuronal protection. [32][33][34] As a naturally occurring compound, melatonin has potential effects on inhibiting autophagy through a redox-mediated scavenge of free radicals and lipid peroxidation, 35 as well as its well-known antioxidant properties. 36 Emerging evidence suggests that melatonin can be used as a neuroprotective agent in the rodent models of PD 32,37,38 by ameliorating the dysfunction of mitochondria, [39][40][41][42] blocking CASP3 (caspase 3, apoptosis-related cysteine peptidase) activation and cellular apoptosis, 43 and protecting TH (tyrosine hydroxylase)-positive nerve terminals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both melatonin and SIRT1 display antiinflammatory properties, 28,29,[64][65][66] and have been shown to be neuroprotective 29,51,67 . Many details are known on antioxidative/antinitrosative actions of melatonin 30,[68][69][70] . Notably, antioxidative protection is strongly related to the circadian system, which includes but also exceeds the rhythmicity of melatonin 45,71 .…”
Section: Depressive Disorders Neurodegeneration and The Protective Rmentioning
confidence: 99%
“…Low-grade oxidative stress and neuroinflammation typically precede clinical symptoms of neurodegeneration 27 . Details concerning the relationship between oxidative/nitrosative stress, inflammation and neurodegeneration have been outlined and reviewed elsewhere [28][29][30] . Numerous other findings that have been repeatedly reviewed, meta-analyzed or studied on a broad scale have shown that sleep loss can be associated with depressive disorders 18,19,[31][32][33][34][35] and neurodegeneration 4,[36][37][38] .…”
Section: Consequences Of Sleep Disturbancesmentioning
confidence: 99%